1995
DOI: 10.1002/j.1460-2075.1995.tb07185.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative disorder and imbalanced T-helper response in C/EBP beta-deficient mice.

Abstract: C/EBP beta is considered a key element of interleukin‐6 (IL‐6) signalling as well as an important transcriptional regulator of the IL‐6 gene itself. We describe here how mice lacking C/EBP beta develop a pathology similar to mice overexpressing IL‐6 and nearly identical to multicentric Castleman's disease in human patients, with marked splenomegaly, peripheral lymphadenopathy and enhanced haemopoiesis. Humoral, innate and cellular immunity are also profoundly distorted, as shown by the defective activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
353
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(370 citation statements)
references
References 35 publications
15
353
1
Order By: Relevance
“…C/EBP␤ is a member of the leucine zipper family of CCAAT enhancerbinding proteins. All members of this family are important regulators of gene expression, particularly involved in inflammatory response and energy metabolism (44,36). C/EBP␤ is present in the majority of cells in two main isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBP␤ is a member of the leucine zipper family of CCAAT enhancerbinding proteins. All members of this family are important regulators of gene expression, particularly involved in inflammatory response and energy metabolism (44,36). C/EBP␤ is present in the majority of cells in two main isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…The TNF-␣ promoter, like the HIV-1 LTR, is strongly repressed by engineered expression of the inhibitory C/EBP␤ in monocytes (68). C/EBP␤ knockout mice, but not mice deficient in both IL-6 and C/EBP␤, develop a lymphoproliferative disease associated with high levels of IL-6 (69,70), suggesting that C/EBP␤ is an important negative regulator of IL-6 production in vivo. Finally, aerosolized IFN-␣ inhibits IL-6 and TNF-␣ production in the lungs of patients with tuberculosis (71).…”
Section: Discussionmentioning
confidence: 99%
“…For example, two groups have reported the targeted disruption of the c/ebp␤ gene (51,52) and have shown that this mutation has only minor effects on the expression of inflammatory cytokine genes. These results are surprising in light of previous data showing that C/EBP␤ plays a critical role in the expression of genes such as interleukin-1, interleukin-6, and monocyte chemoattractant protein-1 in cell lines (26,(53)(54)(55), and suggest that a redundant C/EBP activity compensates for the absence of C/EBP␤ in knockout animals.…”
Section: Discussionmentioning
confidence: 99%